Analysis of The Effect of The Implementation of The Behavior Based Safety (BBS) Program By Company Management on Labor Behavior At PT. HYZ - Putri, Ica Audia; Wiguna, Yifrans Sastra; Purba, Rosita Hanna Sri Yuliani Boru; Fajar, Achmad; Hidayat, Ilham; Ramadhan, Muhammad Rizky; Zuhair, Fitrah Hanan; Malik, Anis Rohmana (Jurnal Multidisiplin Indonesia, 2024)
HYZ Company is a goods shipping and logistics company in the maritime sector with a significant risk of work accidents, especially in the Occupational Health and Safety aspect. The company has implemented a Behavior Based Safety (BBS) program since 2011 to reduce the risk of accidents. This program is designed to increase safe behavior in the workplace and reduce accident incidents. Although BBS is known to reduce work accidents by up to 40-75%, HYZ Company has not conducted an in-depth analysis to determine the extent to which the implementation of this program affects the level of compliance with Occupational Health and Safety principles, including the use of personal protective equipment (PPE), safe work procedures and other safety practices. This study aims to evaluate the effectiveness of BBS at HYZ Company in the context of Occupational Health and Safety, focusing on changing workers' behavior and levels of compliance with safety standards. The results of this research can help companies strengthen their Occupational Health and Safety systems and reduce the risk of accidents while promoting a sustainable safety culture. With a better understanding of the impact of BBS on Occupational Health and Safety compliance, HYZ Company can take more effective measures to ensure worker safety and a safe working environment